Peningkatan Kemampuan Membaca Permulaan Menggunakan Media Aplikasi Marbel Pada Anak Disabilitas Intelektual Ringan - Wiwik Sugiarti; Rahmahtrisilvia Rahmahtrisilvia; Zulmiyetri Zulmiyetri; Syari Yuliana (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to improve early reading skills and to describe the learning process through the use of the Marbel application for students with mild intellectual disabilities. The study employed Classroom Action Research (CAR) and was conducted at SLB Negeri Simalungun. The research subjects were two fifth-grade students with mild intellectual disabilities, identified as SA and VL. Based on the initial assessment, students’ early reading skills were at a low level, with achievement percentages of 35% for SA and 30% for VL.The research was implemented in two cycles, each consisting of planning, action, observation, and reflection stages. The findings indicated a gradual improvement in the learning process. In Cycle I, students showed increased focus, interest, and ability to recognize letters and syllables, although intensive teacher guidance was still required. In Cycle II, the learning process became more effective, as indicated by higher student participation, increased independence, and improved reading fluency. In terms of effectiveness, early reading skills improved to 78% for both students in Cycle I, and increased significantly in Cycle II, reaching 93% for SA and 90% for VL. The results demonstrate that the Marbel application is effective in improving both the learning process and early reading outcomes for students with mild intellectual disabilities.